Binding to histo-blood group antigen-expressing bacteria protects human norovirus from acute heat stress - Li, Dan; Breiman, Adrien; le Pendu, Jacques; Uyttendaele, Mieke (Frontiers in Microbiology, 2015)
This study aims to investigate if histo-blood group antigen (HBGA) expressing bacteria have any protective role on human norovirus (NoV) from acute heat stress. Eleven bacterial strains were included, belonging to Escherichia coli, Enterobacter cloacae, Enterobacter aerogenes, Clostridium difficile, Bifidobacterium adolescentis, and Bifidobacterium longum. HBGA expression of the bacteria as well as binding of human NoV virus-like particles (VLPs, GI.1 and GII.4 strains) to the bacteria were detected by flow cytometry. NoV VLPs pre-incubated with HBGA expressing or non-HBGA expressing bacteria were heated and detected by both direct ELISA and porcine gastric mucin-binding assay. The NoV-binding abilities of the bacteria correlated well with their HBGA expression profiles. Two HBGA expressing E.coli (LMG8223 and LFMFP861, both GI.1 and GII.4 binders) and one non-HBGA expressing E.coli (ATCC8739, neither GI.1 nor GII.4 binder) were selected for the heat treatment test with NoV VLPs. Compared with the same cell numbers of non-HBGA expressing E.coli, the presence of HBGA-expressing E.coli could always maintain higher antigen integrity, as well as mucin-binding ability of NoV VLPs of both GI.1 and GII.4 after heat-treatment at 90°C for 2 min. These results indicate that HBGA-expressing bacteria may protect NoVs during the food processing treatments, thereby facilitating their transmission.